Interaksi Ekspor, Impor dan Inflasi Dalam Mempengaruhi Nilai Tukar Dollar - Emmanuella Vania Tunjung; Ana Kadarningsih (MANAJEMEN, 2025)
This research analyzes the influence of the interaction between exports, imports and inflation on the dollar exchange rate against the rupiah. Using a quantitative approach, secondary data obtained from the Central Statistics Agency and Bank Indonesia during the period 2013 to 2023 were analyzed using census sampling techniques, producing 132 monthly data. The analysis was carried out with Eviews 13 through various statistical tests, including heteroscedasticity tests, autocorrelation, multicollinearity, multiple linear regression, as well as the F test and T test. The research results show that exports have a positive effect on the exchange rate in the long term, although in the short term they can have a negative impact. Imports have a negative influence on the rupiah exchange rate, where an increase in imports has the potential to cause a trade balance deficit and weaken the exchange rate. Inflation shows a negative influence on the exchange rate in the short term, but can contribute positively to strengthening the exchange rate in the long term if balanced with appropriate monetary policy. This research recommends that the government strengthen export policies, manage imports selectively, and maintain stable inflation to support exchange rate stability